Changing patterns in genebank acquisitions of crop genetic materials: An analysis of global drivers and potential consequences - Mekonnen, Dawit Kelemework; Spielman, David J. (Elsevier, 2021)
During the past two decades, a series of global changes affecting genetic resource conservation, use, and exchange have entered into force: the 2004 International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA), and more recently, the 2014 Nagoya Protocol on Access and Benefit Sharing (NP), a follow-on to the 1993 Convention on Biological Diversity (CBD). This paper characterizes the changing landscape governing international exchanges of plant genetic resources for food and agriculture (PGRFA). Emphasis is placed on understanding how global and national changes associated with the CBD and ITPGRFA are significantly associated with the movement of genetic resources to draw lessons about the potential effects of the NP. We examine crop-specific historical trends in genebank acquisitions, changes in germplasm exchange networks over time, and correlates of such exchanges for seven crops that are important to food security in many developing countries. We observe sharp declines in genebank acquisitions in 1993 (when the CBD came into effect) followed by reductions in germplasm exchange network sizes. These trends and patterns change after 2004 (when the ITPGRFA came into effect), but only for some crops. We also find that a country’s membership in the CBD is closely associated with reductions in genetic resource flows, while ITPGRFA membership has an opposite association. Despite important crop and country variations, results suggest the considerable influence of both the CBD and ITPGRFA, further suggesting that the NP may affect global PGRFA flows in a potentially negative and unintended manner.